Robust Load Frequency Control in Hybrid Microgrids Using Type-3 Fuzzy Logic Under Stochastic Variations - Turk, Ismail; Kilic, Heybet; Haydaroglu, Cem; Top, Ahmet (Mdpi, 2025)
This paper presents a type-3 fuzzy logic (T3-FL)-based controller for Load Frequency Control (LFC) in microgrids, focusing on addressing the challenges of renewable energy integration. The integration of renewable sources such as wind and solar leads to power fluctuations and frequency deviations that compromise system stability. The proposed T3-FL controller incorporates advanced features like online adaptation of membership functions and enhanced computational capacity to manage uncertainties in renewable power generation and load variations. The design principles prioritize robustness, adaptability to stochastic variations, and effective frequency stabilization. Simulation results demonstrate that the T3-FL controller significantly improves the microgrid's stability by efficiently mitigating frequency fluctuations across multiple dynamic scenarios.
Keywords: type-3 fuzzy logic control; micro grids; frequency control; stochastic variations